Acne vulgaris: Prevalence, predictors, and factors influencing quality of life of female medical students at King Abdulaziz University, Jeddah - Nahla Khamis Ibrahim; Sarah Abdulaziz Nagadi; Haifa Jamal Idrees; Logain Ghazi Alghanemi; Rawan Ishaq Essa; Walaa Sadik Gari (Wolters Kluwer Medknow Publications, 2019)
Context: Acne vulgaris is the most frequent skin condition that reduces patients' quality of life (QOL). Aims: The aim of the study is to determine the prevalence, clinical manifestations, predictors, and factors that influence QOL of female medical students with acne at King Abdulaziz University Hospital (KAUH), Jeddah. Settings and Design: A cross-sectional design was conducted at KAUH, Jeddah. Subjects and Methods: Four-hundred participants were selected through a stratified random sampling technique during the educational year 2016/2017. Data collection included the "Acne-Specific Quality of Life Questionnaire (Acne-QOL)" and "Hospital Anxiety and Depression Scale (HADS)." Clinical examination was conducted by a female clinician, with grading of acne by the global acne grading system. Statistical Analysis Used: Descriptive and inferential statistics were done. Logistic regression analysis was conducted. Results: The prevalence of acne among medical students was 58.8%. Combined type of acne was the most common clinical presentation. Predictors of acne were stress (P < 0.001), menstrual flaring (P < 0.001), and family history of the condition (P < 0.01). Females with severe acne had the lowest score (worse QOL) of all QOL domains compared to others (P < 0.05). Most of QOL domains were lower among students with psychological problems, anxiety, and depression (P < 0.5). Conclusions: Acne is prevalent among female medical students. Stress, menstrual flaring, and family history were the predictors. Acne-QOL was influenced by the severity of acne, psychological problems, anxiety, and depression. Screening of acne, with holistic management approach (by dermatologists and psychologists), is recommended.